Istilah Proses Pembuatan Gula Merah Masyarakat Desa Canduk Kabupaten Banyumas (Kajian Etnolinguistik) - Nur Zahwa, Alifia; Rosidin, Odien (Sutasoma : Jurnal Sastra Jawa, 2024)
Canduk Village is famous as one of the villages in the Banyumas Regency area as the best brown sugar producing area with a process that still uses hereditary methods to make it. In the manufacturing process, there are several terms commonly used by the people of Canduk village to recognize things related to making brown sugar. This research aims to analyze and describe the terms used in the process of making brown sugar in the Canduk Village community, Banyumas Regency using an ethnolinguistic study approach. The research uses descriptive-qualitative research methods and theoretical approaches such as ethnolinguistic approaches, semantic approaches and linguistic structural approaches. The results of the analysis are in the form of words in the form of lingual units in the form of basic words, compound words, phrases, lexical meaning and cultural meaning of the process of making brown sugar, the meaning of local wisdom from the stages carried out from generation to generation, preservation of traditional pagan ingredients, terms in lingual units which are used as a marker in each form of term it produces.